UJI AKURASI SUPPORT RESISTANCE BERBASIS DATA CANDLESTICK PADA INDUSTRI PERTAMBANGAN YANG TERDAFTAR DI INDEKS LQ45 - Reeves, Octavian G.; Saerang, Ivonne S.; Maramis, Joubert B. (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2019)
The capital market is one indicator of a country's economic progress, which contributes to the economic development of a country. Which can be described as a country's wheels, the source of funds for companies that are the support of a country. This research was conducted with the goals of studying accuracy support resistance by using Fibonacci retracement indicators based on candlestick stock price movements. The type of research used consists of a type of quantitative research using secondary data that contains a graph of the stock price of the LQ45 index mining sector which then carried out a different sample dependent test.The results of this study indicate that the support and resistance on the Fibonacci Retracement indicator has a difference with the selection price so that it can complete estimates of inaccurate support resistance.